Detecting adaptive changes in gene copy number distribution accompanying the human out-of-Africa expansion - Moritz Otto; Yichen Zheng; Paul Grablowitz; Thomas Wiehe (Human Genome Variation)
Abstract Genes with multiple copies are likely to be maintained by stabilizing selection, which puts a bound to unlimited expansion of copy number. We designed a model in which copy number variation is generated by unequal recombination, which fits well with several genes surveyed in three human populations. Based on this theoretical model and computer simulations, we were interested in determining whether the gene copy number distribution in the derived European and Asian populations can be explained by a purely demographic scenario or whether shifts in the distribution are signatures of adaptation. Although the copy number distribution in most of the analyzed gene clusters can be explained by a bottleneck, such as in the out-of-Africa expansion of Homo sapiens 60–10 kyrs ago, we identified several candidate genes, such as AMY1A and PGA3, whose copy numbers are likely to differ among African, Asian, and European populations.